DIFFERENCES IN THE EFFECT OF INTERVAL TRAINING METHOD AND REPETITION TRAINING METHOD ON SWIMMING RESULTS 50 METRES FREESTYLE IN EAGLE ATHLETES AQUATICS FIELD IN 2022 - Wardiman Berkat Mendrofa; Muhammad Nustan Hasibuan (Universitas Negeri Medan, 2022)
This study aims to determine the influence of the Interval training method and the Reps training method on improving the results of the 50-meter freestyle swimming in the Medan KU I Aquatic Eagle Men's Athletes in 2022. The research method used in this study is the experimental method. The total population used in the inn study was 11 people. The sampling technique used is Purposive Sampling. The number of samples used was 8 people. In this sampling, 2 groups were divided into 2 groups by means of matching ordinal pairing subjects. The study was carried out for 6 weeks with a frequency of exercise 3 times each week. The first hypothesis analysis is that there is a significant influence of the Interval training method on the increase in 50-meter freestyle swimming results in the Medan KU I Aquatic Eagle Athletes in 2022, a t-count of the > t-table (6.54> 3.18), based on hypothesis testing criteria, in this study there is a significant influence of the Interval training method on the results of 50-meter freestyle swimming in the Men's Athletes of the Medan KU I Aquatic Eagles in 2022.The second hypothesis analysis is that there is a significant influence of the Repetition training method on the improvement of 50-meter freestyle swimming results in the Medan KU I Aquatic Eagle Athletes in 2022, obtained t-count> t-table (3.98>3.18), based on hypothesis testing criteria, in this study there is a significant influence of the Interval training method on the results of 50-meter freestyle swimming in the Men's Athletes of the Medan KU I Aquatic Eagles in 2022.The third hypothesis analysis is that the Interval training method has more influence on the increase in the results of 50-meter freestyle swimming in the Medan KU I Aquatic Athletes in 2022, where the results of the comparison of the average results of the increase in post-test data variable X1 > the variable X2 (7.86 > 5.65) then from these results the interval training has more influence on increasing the speed of freestyle swimming 50 meters in the Men's Athletes of the Medan Aquatic Eagles in 2022.